Low-dose oral pregabalin is not effective enough to control the acute post-thoracotomy pain - Swati Dogra; Altaf Hussain Mir; Suhail Sidiq; Rohey Jan; Khan, Talib; Syed Amer Zahoor; Hakeem Zubair Ashraf; Shaqul Qamar Wani; Sandeep Verma; Guddi Devi; et al. (Asian Journal of Medical Sciences, 2025)
Background: Acute post-thoracotomy pain (APTP) is severe and can lead to various respiratory complications if left untreated. Epidural (Ep) analgesia is the gold standard for APTP relief. Aims and Objectives: The aims and objectives of this study were to study the impact of low-dose oral pregabalin 75 mg on APTP. Materials and Methods: 100 patients were randomized into two groups (Group P and C). The Group P, study group received pregabalin 75 mg per oral preoperatively and for 2 days postoperatively. Group C received no medication. All the patients received thoracic Ep as a standard practice. Postoperatively Visual Analog Scale (VAS), modified Ramsay sedation scoring (RSS), number of Ep top-ups, and adverse effects were noted. Results: The age and gender of the patients in both the groups were comparable. No statistically significant difference was found between Group P versus Group C with regard to VAS score, RSS, number of Ep top-ups, and any adverse effects. VAS between the groups at 4 h, 36 h, and 48 h postoperatively were statistically significant differences (P<0.05). VAS score at 48 h was not statistically significant (P>0.05). Ep analgesia was sufficient in both the groups and no patient in either group required intravenous fentanyl as rescue analgesia. No adverse effects were reported in any groups (P>0.05). Conclusion: Oral Pregabalin 75 mg did not reduce the severity of acute postoperative pain after thoracotomy. Study with higher doses of pregabalin needs to be carried out to evaluate the benefits of pregabalin on APTP.